2021
DOI: 10.3389/fphar.2021.616318
|View full text |Cite
|
Sign up to set email alerts
|

Huanglian Jiedu Decoction in the Treatment of the Traditional Chinese Medicine Syndrome “Shanghuo”–An Intervention Study

Abstract: “Shanghuo” (“excessive internal heat”) is caused by exuberant endogenous fire, which does not have a comprehensive and systematic traditional Chinese medicine theory. In previous study, we had evaluated the therapeutic effect of Huanglian Jiedu Decoction (HLJDD) (granule) on patients with “Shanghuo”, however, the specific mechanism was not clear, which need further exploration. To explain its intervention mechanism, we select 57 patients with oral diseases caused by “Shanghuo” and 20 health volunteers to divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Through plasma metabolomics analysis, it was concluded that energy metabolism and amino acid metabolism were greatly influenced by constipation. Pyruvate is the final product of glycolytic pathway and participates in TCA cycle 33 . The decrease of pyruvate and the increase of glucose in plasma of constipated rats, as well as negative correlations of the two metabolites, indicate that glycolytic pathway was perturbed, which in turn affects energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Through plasma metabolomics analysis, it was concluded that energy metabolism and amino acid metabolism were greatly influenced by constipation. Pyruvate is the final product of glycolytic pathway and participates in TCA cycle 33 . The decrease of pyruvate and the increase of glucose in plasma of constipated rats, as well as negative correlations of the two metabolites, indicate that glycolytic pathway was perturbed, which in turn affects energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a strong positive correlation was not observed between the efficacy of traditional Chinese medicine and the contents of the main active components. Nevertheless, there are numerous forms of effective components of Traditional Chinese medicine, and self-precipitation in precipitate compatibility could be the “drug storage warehouse” of effective components ( Luo et al, 2021 ). After entering the body, the precipitates are intercepted and absorbed by intestinal villi, and become active components or precursors again under the action of intestinal microorganisms and enzymes, thereby acting on intestines, microorganisms, and diffusing into the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a combination of the two herbal components can considerably clear heat, dryness, and dampness. Therefore, both herbs form a classical drug pair for clearing heat, dryness, and dampness in clinical practice ( Chan et al, 2020 ; Luo et al, 2021 ). According to traditional Chinese medicine practice, Radix Scutellariae and Rhizoma Coptidis decoction is mostly prepared in the form of a combined decoction ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…132 Moreover, it is noteworthy that HJD can significantly reduce the levels of inflammatory factors such as TNF-α and IL-8, effectively suppressing immune and inflammatory responses. 133 , 134 Simultaneously, it significantly alters the gene expression profile of SHR, involving multiple cellular functions like smooth muscle contraction regulation, endothelial cell Ca(2+) balance, and nitric oxide (NO) pathways. 135 In addition to HJD, the active components of Taohong Siwu Decoction (TSD) also demonstrate remarkable effects in the treatment of cardiovascular diseases.…”
Section: Microbial Targeted Therapymentioning
confidence: 99%